Anti-nuclear antibodies in patients with breast cancer. (14th June 2018) - Nisihara, R; Machoski, M C C; Neppel, A; Maestri, C A; Messias-Reason, I; Skare, T L
Summary: To study the prevalence of anti-nuclear antibodies (ANA) in breast cancer patients and its association with tumour characteristics. Ninety-one patients with breast mass detected by image studies and assigned to conduct diagnostic biopsy and eventual surgical treatment were studied for demographical, tumour data and presence of ANA. Serum of positive ANA patients was screened for the extractable nuclear antigen (ENA) profile. As comparison, 91 healthy individuals matched for age and from the same geographical area were included. In this sample 72 of 91 (79·1%) had malignant lesions (83% ductal infiltrative carcinoma). ANA was positive in 44·4% of patients with malignant tumour and in 15·7% of those with benign lesions (malignant versus benign with P = 0·03). Controls had ANA positivity in 5·4%, and when compared with tumour samples showed P < 0·0001. The most common immunofluorescence pattern was a fine dense speckled pattern. In the ANA-positive patients with malignant lesions, seven had positivity for ENA profile (three for anti-RNP and anti-Sm, one for just anti-RNP, two for anti-Ro and anti-La e two for just anti-La). It was not possible to associate ANA positivity with tumour histological characteristics or staging or with patient's age. A negative association of ANA with hormonal (oestrogen or oestrogen plus progesterone) receptor status was found ( P = 0·01). In this sample, there was a high prevalence of ANA positivity in breast cancer patients with a negative association with the presence of hormonal receptors. More studies are needed to understand the real value of this finding. Graphical Abstract: